Media Buku Kesehatan Ibu dan Anak Mempengaruhi Self Efficacy Ibu Hamil dalam Pemanfaatan Antenatal Care - Miranti Mandasari; Yusriani Yusriani; Sitti Patimah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
The Maternal and Child Health Book is one of the media used by health workers in educating pregnant women so that they can increase self-efficacy during pregnancy, childbirth and the puerperium. This study aims to analyze the influence of the MCH book media on the self-efficacy of pregnant women in the use of antenal care services at Lauwa Health Center, Gowa Regency. This type of research was a quasi experiment, with a pre post test without control group design. The sample were selected by purposive sampling method during June-July 2020 with a sample size of 35 respondents. Data were analyzed by t-test. The results showed that the MCH book media had an effect on pregnant self-efficacy in the use of antenatal care services, with a p-value